Simple sequence repeat (SSR) diversity of cassava in South, East and Central Africa in relation to resistance to cassava brown streak disease - Pariyo, A.; Tukamuhabwe, Phineas; Baguma, Yona K.; Kawuki, Robert S.; Alicai, Titus; Gibson, P.J.; Kanju, E.; Wanjala, Bramwel W.; Harvey, Jagger J.W.; Nzuki, I.; Rabbi, Ismail Y.; Ferguson, Morag E. (Academic Journals, 2013)
This study was conducted to: (1) determine the amount and structure of the genetic diversity of cassava in southern, eastern and central (SEC) Africa using simple sequence repeat (SSR) markers, (2) determine the frequency and distribution of alleles putatively associated with resistance to cassava brown streak disease (CBSD) derived from the variety ‘Namikonga’, and (3) examine the genetic relationships among some CBSD resistant genotypes. The major findings from this study were: (1) little genetic differentiation was confirmed among countries (7%) with the majority of variation distributed among individuals (93%), (2) the frequency of alleles putatively associated with resistance to CBSD was found to be generally low (0.2 to 0.5) but widely dispersed in the cassava germplasm of the SEC Africa region implying that if validated the markers will be useful for marker-assisted breeding on a broad scale, (3) several distinct putative sources of resistance to CBSD seem to be present in the cassava germplasm of SEC Africa offering the potential to pyramid genes for more effective and durable resistance and (4) it may be more informative to assess cassava diversity in the SEC Africa region based on pedigree (if known) or genetic relatedness, rather than geographical origin.